The Impact of Craniofacial Skeletal Patterns on Sleep Quality and Oral Health-Related Quality of Life Among Adults - Yenidunya D; Yilmaz B (Nature and Science of Sleep)
Deniz Yenidunya,1 Berza Yilmaz2 1Department of Orthodontics, Institute of Health Sciences, Bezmialem Vakif University, Istanbul, Turkiye; 2Department of Orthodontics, Faculty of Dentistry, Bezmialem Vakif University, Istanbul, TurkiyeCorrespondence: Deniz Yenidunya, Department of Orthodontics, Bezmialem Vakif University, Adnan Menderes Blv., Fatih, Istanbul, 34093, Turkiye, Tel +905397870278, Email drdenizyenidunya@gmail.comPurpose: This study aimed to assess the possible impact of sagittal and vertical skeletal patterns on sleep quality and oral health-related quality of life (OHRQoL).Patients and Methods: Following the acquisition of their written informed consent, 330 patients who applied for orthodontic treatment and who met the inclusion requirements were invited to take part in the study by completing the following questionnaires: Beck Depression Inventory (BDI), Pittsburgh Sleep Quality Index (PSQI), and Oral Health Impact Profile (OHIP-14). According to criteria like incomplete questionnaires, BDI score above 17 and body mass index higher than 30, 50 patients’ data were excluded. Two hundred and eighty participants were classified according to their sagittal and vertical patterns and the hyoid bone distance to the mandibular plane (GoGn) and anterior cranial base (SN). Oral health-related quality of life and its components, sleep quality and its components were compared between groups.Results: The PSQI scores for the sagittal and vertical groups did not significantly differ from each other, except for the normodivergent and hyperdivergent groups’ total scores. It was observed that when the Hyoid-SN line distance decreased; the sleep quality decreased with an increase in the “sleep disturbance” and “daytime dysfunction”. Neither the Hyoid-GoGn distance nor vertical or sagittal patterns were found to be related to OHRQoL. There was a significant correlation between OHIP-14 and PSQI.Conclusion: Our findings showed that various vertical and sagittal craniofacial features would not affect the OHRQoL scores. PSQI scores appear to be unaffected by the sagittal pattern, but a significant difference was noted in the total score between groups formed considering the vertical pattern.Keywords: sleep quality, oral health, orthodontics, quality of life